TANGGUNG JAWAB HUKUM TENAGA PERAWAT TERHADAP MALPRAKTIK KEPERAWATAN, DENGAN FOKUS PADA STUDI KASUS DI RUMAH SAKIT WATES HUSADA - kristanto setyo nugroho; Zainal Mustofa; Finici Dhanur Aran (Universitas Duta Bangsa Surakarta, 2025)
Nurses are at the forefront of the health care system and play a strategic role in ensuring the safety and quality of life of patients. However, in practice, nurses often face legal risks due to allegations of malpractice that occur due to negligence, exceeding authority, or non-compliance of actions with standard operating procedures. This study aims to analyze the form of legal responsibility of nurses for malpractice cases and evaluate the application of positive law in the context of health services in Indonesia, especially through a case study at Wates Husada Hospital. The method used is a normative legal approach with juridical analysis of legislation, legal doctrine, and related decisions. The results showed that the legal responsibilities of nurses include criminal, civil, and disciplinary aspects, the implementation of which still faces challenges in terms of legal understanding, medical documentation systems, and internal supervision mechanisms. This study emphasizes the importance of legal briefing for nurses, strengthening professional ethics, and reforming the risk management system in hospitals to create professional, safe, and lawful nursing practices